If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4x+6)*4=88
We simplify the equation to the form, which is simple to understand
(4x+6)*4=88
Reorder the terms in parentheses
(+16x+24)=88
Remove unnecessary parentheses
+16x+24=88
We move all terms containing x to the left and all other terms to the right.
+16x=+88-24
We simplify left and right side of the equation.
+16x=+64
We divide both sides of the equation by 16 to get x.
x=4
| 5+35x=28x+7 | | 4(0.75n+1)=5-2(n-0.50) | | 16y-27=13 | | x^2+24.933x-305.4=0 | | -7+-w=-10 | | 6x+0.4=42.4 | | x^2+25x-305=0 | | 2x+35+x-2=180 | | x^2-25x+305=0 | | -c+4c+7=7-c+8c | | -4+2s=4 | | 10+6k= | | 12x=9.12 | | -4=-12+4n | | -8+1x=-1x+20 | | a3*a2/a5= | | 7x+4y=61 | | 14m+5n-4m+9n= | | 17-20b=4(-13-5b) | | q^2-16q+275=0 | | 4 = v-2+ 5 | | 16/140=x/60 | | 5b+6=132-10 | | (2x+1)+x+13=72 | | -6(x-7)=66 | | 14m+5n-4m+9m= | | 6r+3t=-18 | | 2x+3(-7x+4)=145 | | 6r+3t=-13 | | 3+4b=-13 | | 2(3a-6)=3(2a-4) | | 5=-7+-t |